2012
DOI: 10.1080/10256016.2012.677042
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the protein and the energy metabolism in man during a wintering in Antarctica

Abstract: During the 29th Soviet Antarctic Expedition in Novolazarevskaya from March 1984 to March 1985, the protein and energy metabolisms were studied in six expeditioners from the German Democratic Republic. The investigations were carried out at the beginning of the expedition (May), during the polar night (July) and during the polar day (December). The effect of a special stress situation (sledge trek in April 1984) was investigated in one subject. The stable nitrogen isotope (15)N was used to study the protein met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…Other studies of seasonal changes in metabolic rates in high latitude environments have been conducted among military and scientific personnel stationed in Antarctic bases (Duncan, ; Junghans et al, ; Lewis et al, ; Reed et al, ; Wilson, ) or among urban populations living in northern cities in Europe (Haggarty et al, ; Plasqui et al, ) and Asia (Kashiwazaki, ; Osiba, ). This research provides an inconsistent picture of the impact of seasonal changes in temperature on metabolic rates, with some studies showing significant winter‐time increases in metabolic rate (Kashiwazaki, ; Osiba, ; Plasqui et al, ; Reed et al, ), while others have shown the opposite trend (Duncan, ; Junghans et al, ; Wilson, ), or no significant seasonal effect (Haggarty et al, ; Lewis et al, ; Park et al, ). Some of the differences in seasonal patterns of metabolic rates among high latitude groups likely reflect variation in the severity of climate and differences in activity patterns and cold exposure during the winter months.…”
mentioning
confidence: 99%
“…Other studies of seasonal changes in metabolic rates in high latitude environments have been conducted among military and scientific personnel stationed in Antarctic bases (Duncan, ; Junghans et al, ; Lewis et al, ; Reed et al, ; Wilson, ) or among urban populations living in northern cities in Europe (Haggarty et al, ; Plasqui et al, ) and Asia (Kashiwazaki, ; Osiba, ). This research provides an inconsistent picture of the impact of seasonal changes in temperature on metabolic rates, with some studies showing significant winter‐time increases in metabolic rate (Kashiwazaki, ; Osiba, ; Plasqui et al, ; Reed et al, ), while others have shown the opposite trend (Duncan, ; Junghans et al, ; Wilson, ), or no significant seasonal effect (Haggarty et al, ; Lewis et al, ; Park et al, ). Some of the differences in seasonal patterns of metabolic rates among high latitude groups likely reflect variation in the severity of climate and differences in activity patterns and cold exposure during the winter months.…”
mentioning
confidence: 99%
“…During wintering in Antarctica, the protein and energy metabolism were studied in six expeditioners [41]. The investigations were carried out at the beginning of the expedition, during the two and a half month polar night and during the polar day.…”
Section: The Protein Metabolism Under Stress Conditionsmentioning
confidence: 99%
“…Concerning the N and protein metabolism studied by single [16,20,21,24,28,30,33,35,36,40,41,43,44] or multiple pulse [5,29], infusion [31,32,34] and priming [13,42] tracer techniques, we have investigated various metabolic states:…”
Section: Practical Applicationsmentioning
confidence: 99%
See 2 more Smart Citations